2012
DOI: 10.1002/art.34596
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA‐31 as a novel regulator contributing to impaired interleukin‐2 production in T cells from patients with systemic lupus erythematosus

Abstract: Objective. MicroRNAs (miRNAs) function to finetune the control of immune cell signaling. It is well established that there are abnormalities in the interleukin-2 (IL-2)-related signaling pathways in systemic lupus erythematosus (SLE). The miR-31 micro-RNA has been found to be markedly underexpressed in patients with SLE, and thus the present study was undertaken to investigate the role of miR-31 in IL-2 defects in lupus T cells.Methods. Expression levels of miR-31 were quantitated using TaqMan miRNA assays. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 60 publications
3
62
0
Order By: Relevance
“…In addition, lupus-associated miRNAs are reported to be differentially expressed in male and female lupusprone NZB/NZW F1 mice (100). Lupus-associated miRNAs regulate the expression of a number of genes that are important for immune responses, including FOXP3, RHOA, FCGR1, and others (101)(102)(103)(104). It is not entirely clear what drives differential expression of miRNAs in males and females.…”
Section: Chromosome-encoded Micrornas In Sexual Dimorphismmentioning
confidence: 99%
“…In addition, lupus-associated miRNAs are reported to be differentially expressed in male and female lupusprone NZB/NZW F1 mice (100). Lupus-associated miRNAs regulate the expression of a number of genes that are important for immune responses, including FOXP3, RHOA, FCGR1, and others (101)(102)(103)(104). It is not entirely clear what drives differential expression of miRNAs in males and females.…”
Section: Chromosome-encoded Micrornas In Sexual Dimorphismmentioning
confidence: 99%
“…The regulation of il-2 is complex, but mir-31 and mir-155 contributes to its expression. Fan et al demonstrated that decreased mir-31 expression positively correlates with decreased il-2 synthesis in sle T cells 111 . Further experiments showed that mir-31 increases il-2 promoter activity by altering the expression of the nuclear factor of activated T cells (NFaT) (ref.…”
Section: Pathologies In Adaptive Immunity In Sle and Mirs T Cells MImentioning
confidence: 99%
“…as mentioned above, il-2 -a cytokine that is essential for Treg survivalis down-regulated by mir-31 or mir-155 in sle (ref. 111,112 ). moreover, mir-31 can suppress Foxp3 expression directly by binding to 3'UTr mrNa (ref.…”
mentioning
confidence: 99%
“…Furthermore, it has been reported that regulation of miR‐31a‐5p expression could be used to modulate senescence‐related pathological conditions such as cancer, and the aging process (Capri et al., 2017; Cho, Dimri, & Dimri, 2015), which highlights us the important role of miR‐31a‐5p in cellular senescence. Moreover, according to a previous study, miR‐31a‐5p controls osteoclast formation and facilitates IL‐2 production in T cells by targeting RhoA (Fan et al., 2012; Mizoguchi, Murakami, Saito, Miyasaka, & Kohsaka, 2013). Thus, these findings raise the possibility that miR‐31a‐5p derived from BMSCs regulates both osteoblastogenesis and osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%